Characterization of normal regional myocardial function by MRI cardiac tagging. Issue 1 (12th December 2013) - Del‐Canto, Irene; López‐Lereu, María P.; Monmeneu, José V.; Croisille, Pierre; Clarysse, Patrick; Chorro, Francisco J.; Bodí, Vicente; Moratal, David
<x xml:space="preserve">Abstract</x> Purpose The aim of this study was to establish reference values for segmental myocardial strain measured by magnetic resonance (MR) cardiac tagging in order to characterize the regional function of the heart. Material and Methods We characterized the left ventricular (LV) systolic deformation in 39 subjects (26 women and 13 men, age 58.8 ± 11.6 years) whose cardiological study had not revealed any significant abnormality. The deformation was measured from MR‐tagged (Siemens 1.5T MR) images using an algorithm based on sine wave modeling. Circumferential and radial peak systolic strain values along with the torsion angle and circumferential‐longitudinal (CL) shear were determined in 16 LV segments in order to settle the reference values for these parameters. Results Circumferential strain was highest at the anterior and lateral walls (−20.2 ± 4.0% and −21.8 ± 4.3%, respectively; P < 0.05) and was lowest at the base level (−17.2 ± 3.1% vs. −20.1 ± 3.1% "mid level, " P < 0.05; −17.2 ± 3.1% vs. −20.3 ± 3.0% "apical level, " P < 0.05). Radial strain highest values were from inferior and lateral walls (13.7 ± 7.4% and 12.8 ± 7.8%, respectively; P < 0.05) and it was lowest medially (9.4 ± 4.1% vs. 13.1 ± 4.1% "base level, " P < 0.05; 9.4 ± 4.1% vs. 12.1 ± 4.4% "apical level, " P < 0.05). Torsion angle (counterclockwise when viewed from the apex) increased with the distance from the base (7.9 ± 2.4° vs. 16.8 ± 4.4°, P < 0.05), and the highest and lowest values were found at lateral (medial lateral: 12.0 ± 4.4°, apical lateral: 25.1 ± 6.4°, P < 0.05) and septal wall (medial septal: 3.6 ± 2.1°, apical septal: 8.3 ± 5.3°, P < 0.05), respectively. These differences were found again in CL shear values, around the LV circumference. However, CL shear remained constant with increasing distance from the base (9.1 ± 2.6°, medium and 9.8 ± 2.4°, apex). Conclusion In summary, this study provides reference values for the assessment of regional myocardial function by MR cardiac tagging. Comparison of patient deformation parameters with normal deformation patterns may permit early detection of regional systolic dysfunction. J. Magn. Reson. Imaging 2015;41:83–92. © 2013 Wiley Periodicals, Inc.